ҲӘЎЖАРДЫҢ ЖАНРЛЫҚ ҲӘМ КОМПОЗИЦИЯЛЫҚ ӨЗГЕШЕЛИГИ - Баўатдинова, С.Ж. (ILIM hám JÁMIYET, 2023)
"Havzhar" is one of the rich folk songs that illuminate the traditions of the Karakalpak people. Consisting of traditional folk remedies, it is a part of traditional culture. Samples of traditional poetry also serve in the performance and preservation of any tradition.